Application of cysteinyl prolyl ester for the synthesis of cyclic peptides containing an RGD sequence and their biological activity measurement - Yamada, Akina; Takei, Toshiki; Kawakami, Toru; Taniguchi, Yukimasa; Sekiguchi, Kiyotoshi; Hojo, Hironobu (Frontiers in Chemistry, 2024)
Cysteinyl RGD-peptidyl cysteinyl prolyl esters, which have different configurations at the cysteine and proline residues, were synthesized by the solid-phase method and cyclized by the native chemical ligation reaction. Cyclization efficiently proceeded to give cyclic peptides, regardless of the difference in the configuration. The peptides were further derivatized to the corresponding desulfurized or methylated cyclic peptides at the Cys residues. The inhibition activity to αvβ6 integrin binding was then analyzed by ELISA. The results showed that the activity varied depending on the difference in the configuration and modification of the cysteinyl prolyl ester (CPC) moiety, demonstrating the usefulness of this method in the search for a good inhibitor of the protein–protein interaction.